Increased level of cytokines and matrix metalloproteinases in osteoarthritic subchondral bone - Hulejová, Hana; Baresová, Veronika; Klézl, Zdenek; Polanská, Markéta; Adam, Milan; Senolt, Ladislav (Cytokine, 2007)
OBJECTIVE: The aim of this study was to investigate the expression of several cytokines, matrix metalloproteinases (MMPs), and tissue inhibitor of matrix metalloproteinases (TIMP)-1 in osteoarthritis (OA) and control sera and different joint tissues. METHODS: Serum, synovial fluid, cartilage, synovial and subchondral bone tissues were examined in OA and control subjects. The protein level of tumor necrosis factor (TNF)-alpha, interleukin (IL)-1alpha, IL-8, IL-10 and MMP-2, MMP-3, MMP-9, and TIMP-1 were measured by immunoanalysis. RESULTS: Serum levels of TNF-alpha, MMP-3 and -9 were significantly higher in OA patients than in controls. Conversely, serum IL-10 was decreased in OA patients. CRP was elevated when compared to healthy controls and decreased significantly 6 months after the surgery. In contrast to control samples, OA cartilage and synovium revealed significantly higher MMP-2, -3, -9 and IL-10. IL-1alpha was significantly higher in OA cartilage and IL-8 in OA synovium. Interestingly, MMP-3, -9, TIMP-1 and all tested cytokines were up-regulated in OA subchondral bone. DISCUSSION: This study demonstrates pro-inflammatory condition of OA pathology and supports the idea that vascularized subchondral region may increase the synthesis of cytokines and MMPs leading to degradation of adjacent cartilage.
Keywords: Bones of Lower Extremity; artróza kyčelních kloubů; Female; Cytokines; matrixové metaloproteinasy; C-Reactive Protein; ženské pohlaví; cytokiny; lidé; Inflammation Mediators; kloubní chrupavka; Osteoarthritis, Hip; synoviální tekutina; studie případů a kontrol; Cartilage, Articular; Male; Case-Control Studies; Aged; Matrix Metalloproteinases; Synovial Fluid; mediátory zánětu; C-reaktivní protein; lidé středního věku; senioři; mužské pohlaví; Middle Aged; kosti dolní končetiny; Humans